The smallest quaternary ammonium salts with ether groups for high-performance electrochemical double layer capacitors - Han, Taihee (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
Electrochemical double layer capacitors (EDLCs) are energy storage devices that have been used for a wide range of electronic applications. In particular, the electrolyte is one of the important components, directly related to the capacitance and stability. Herein, we first report a series of the smallest quaternary ammonium salts (QASs), with ether groups on tails and tetrafluoroborate (BF(4)) as an anion, for use in EDLCs. To find the optimal structure, various QASs with different sized head groups and ether-containing tail groups were systematically compared. Comparing two nearly identical structures with and without ether groups, QASs with oxygen atoms showed improved capacitance, proving that ions with oxygen atoms move more easily than their counterparts at lower electric fields. Moreover, the ether containing QASs showed low activation energy values of conductivities, leading to smaller IR drops during the charge and discharge processes, resulting in an overall higher capacitance.